Pengaruh Kualitas Pelayanan dan Kemudahan Dalam Mengakses Informasi Terhadap Peningkatan Kepatuhan Wajib Pajak Orang Pribadi di Kota Palembang - Panggabean, Margaretha Eleora; Pritama, Tiara (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to analyze the influence of service quality and ease of accessing information on increasing individual taxpayer compliance in Palembang City. The data used in this research is primary data. The population in this study are non-employee individual taxpayers registered with the Palembang City KPP. The sampling technique used was the purposive sampling method and 34 samples were obtained. Hypothesis testing is carried out using multiple regression analysis. The results of this research indicate that service quality has no effect on increasing taxpayer compliance and ease of accessing information has an effect on increasing taxpayer compliance.